2022
DOI: 10.1093/jpids/piac119
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Screening Testing Programs for Safe In-person Learning in K–12 Schools

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) screening testing is a recommended mitigation strategy for schools, although few descriptions of program implementation are available. Methods Kindergarten through 12th grade (K–12) students and staff practicing universal masking during the delta and omicron variant waves from 5 schools in Durham, North Carolina and 8 in Kansas City, Missouri participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A systematic review of school-based testing programs reported that cumulative school-based transmission rates among students from December 2019 to September 2020 were low (ie, 0.15%) 21. This review and others suggested that while school transmission is related to community transmission, schools are no riskier for COVID infection than at home or out in the community 16,19,21,22…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…A systematic review of school-based testing programs reported that cumulative school-based transmission rates among students from December 2019 to September 2020 were low (ie, 0.15%) 21. This review and others suggested that while school transmission is related to community transmission, schools are no riskier for COVID infection than at home or out in the community 16,19,21,22…”
mentioning
confidence: 87%
“…21 This review and others suggested that while school transmission is related to community transmission, schools are no riskier for COVID infection than at home or out in the community. 16,19,21,22 Recognizing the utility of school-based testing, the National Institutes of Health's Rapid Acceleration of Diagnostics Underserved Populations (RADx-UP) program awarded $33 million to COVID testing projects in underserved communities. This article describes developing and implementing an approach to support COVID surveillance and reflex testing strategies in partner schools funded under the RADx-UP initiative (OT2HD107543) to facilitate a return to in-person learning.…”
mentioning
confidence: 99%
“…Although children spend most of their awake hours in the school setting, few data are available on the prevalence of respiratory viruses in schools. Surveillance for respiratory viruses other than SARS-CoV-2 has not been widely conducted in primary and secondary schools (2).…”
mentioning
confidence: 99%